Another Calculational Proof of Cantor’s Theorem - Cerioli, Márcia R.; Freitas, Renata de; Viana, Petrucio (Anais do Workshop Brasileiro de Lógica (WBL), 2022)
E. Dijkstra and J. Misra [American Mathematical Monthly, 108:440–443 (2001)] presented a calculational proof of Cantor's Theorem. Their proof is based essentially on the Axiom of Choice. In this note, we present another calculational proof which does not appeal, at least directly, to the Axiom of Choice. Our proof is based only on logical steps and a heuristic guidance analogous to the one used by Dijkstra and Misra in their proof.